IMPLEMENTATION OF RELIGIUSITY HUMANISM EDUCATION IN ISLAMIC RELIGIOUS EDUCATION IN THE ERA REVOLUSI INDUSTRI 4.0 - Nuryami; Imanuddin Abil Fida; Eltom Ishaq Osman Musa (International Journal of Multidisciplinary Reseach, 2025)
This study aims to explore the basic concept of humanism education as education so that children consciously have religious characteristics with an Islamic perspective and have an implementation in the learning process. Then a library research approach is needed by collecting information from relevant reading materials, magazines, books, seminars, and others, after that it is carefully studied and researched, then the data is generalized and sorted based on the suitability of the research theme, then the data obtained from the results of further sorting analyzed in depth with analytical methods. Based on the results of the researcher's analysis that the concept of humanism education is an educational concept originating from the assumption that human beings have almost the same potential, which must be developed intensively and continuously so that religious humanist education has relevance to the era of the industrial revolution 4.0. Humanism education invites students to find solutions to problems encountered with guidance and direction from educators. Implementing this concept emphasizes educators so that they can create a learning environment that is far from elements of coercion, oppression, the hegemony of thought, and attitudes that are far from the universal values of monotheism and humanity.